76.5k views
2 votes
Solve 4x − 5 = 6 for x using the change of base formula log base b of y equals log y over log b.

−4.226
−3.708
5.774
6.292

User Takuto
by
4.9k points

2 Answers

3 votes

Answer:

Explanation:

4^x-5 = 6

Apply the ln rule

x^y = z

(y)*ln(x) = z

4^x-5 = 6

(x-5)*ln(4) = ln(6)

x-5 = ln(6)/ln(4)

x-5 = 1.292

x = 6.292

Therefore, the correct answer is the last option.

!!

User Lee Hesselden
by
5.0k points
3 votes

Answer:

Option 4 - x=6.292

Explanation:

Given : Expression
4^(x-5)=6

To find : Solve the expression using change of base formula?

Solution :

Expression
4^(x-5)=6

Change of base formula is
\log_b y=(\log_a y)/(\log_a b)

Step 1 - Taking log both side in the expression,


\log(4^(x-5))=\log (6)

Apply logarithmic property,
\log a^x=x\log a


(x-5)\log(4)=\log (6)

Step 2 - Taking log one side,


x-5=(\log (6))/(\log(4))

Step 3 - Apply change base formula,


x-5=\log_4 6

Step 4 - Solve,


x=\log_4 6+5


x=1.292+5


x=6.292

Therefore, Option 4 is correct.

User Flavio Caduff
by
4.5k points